2014
DOI: 10.1186/1477-7819-12-365
|View full text |Cite
|
Sign up to set email alerts
|

Role of apparent diffusion coefficients with diffusion-weighted magnetic resonance imaging in differentiating between benign and malignant bone tumors

Abstract: BackgroundBenign and malignant bone tumors can present similar imaging features. This study aims to evaluate the significance of apparent diffusion coefficients (ADC) in differentiating between benign and malignant bone tumors.MethodsA total of 187 patients with 198 bone masses underwent diffusion-weighted (DW) magnetic resonance (MR) imaging. The ADC values in the solid components of the bone masses were assessed. Statistical differences between the mean ADC values in the different tumor types were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 13 publications
6
25
0
6
Order By: Relevance
“…The presented patient also had mixed density in both T1 and T2W images, and contrast enhancement was heterogenous after contrast media injection (Figure 2). DWI is a valuable method for differentiation of a bone lesion that it is benign or malign [9]. The low signal on DWI was detected on MRI in the presented case was thought the lesion was benign nature.…”
Section: Disclosurementioning
confidence: 91%
“…The presented patient also had mixed density in both T1 and T2W images, and contrast enhancement was heterogenous after contrast media injection (Figure 2). DWI is a valuable method for differentiation of a bone lesion that it is benign or malign [9]. The low signal on DWI was detected on MRI in the presented case was thought the lesion was benign nature.…”
Section: Disclosurementioning
confidence: 91%
“…Simple bone cysts, and aneurysmal bone cysts, especially have been reported as having high minimum or mean ADC (around 2.0 × 10 −3 mm 2 /s) because of their higher water content . On the other hand, even if benign, several tumors such as nonossifying fibroma and intraosseous epidermoid are reported as having an ADC of less than 1.0 × 10 −3 mm 2 /s . Extracellular water movement might be restricted due to their dense network of collagen fibers in fibrotic tumors like nonossifying fibromas.…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 99%
“…Extracellular water movement might be restricted due to their dense network of collagen fibers in fibrotic tumors like nonossifying fibromas. Hence, it has been suggested that ADC needs to be interpreted within the context of a tumor's signal intensity on T 2 ‐weighted images (T 2 WI) and DWI . Furthermore, biologically aggressive benign lesions, such as giant cell tumor (GCT), osteoblastoma, and Langerhans cell histiocytosis, have also been reported to have lower minimum and mean ADC, which considerably overlap with the value of malignant lesions …”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 99%
See 2 more Smart Citations